P292 REDEFINING THE EPIDEMIOLOGY OF CARDIAC AMYLOIDOSIS. A SYSTEMATIC REVIEW OF SCREENING STUDIES. (18th May 2022) - Aimo, A; Merlo, M; Porcari, A; Pagura, L; Sinagra, G; Vergaro, G; Emdin, M; Rapezzi, C
Abstract: Background: Over the last years, an algorithm for non–invasive diagnosis of amyloid transthyretin cardiac amyloidosis (ATTR–CA) and novel disease–modifying therapies have prompted an active search of CA in different clinical settings. Methods: We performed a systematic search of screening studies investigating CA. Results: The average prevalence of CA in different settings were as follows: total body scintigraphy with "bone tracers" for non–cardiac reasons (n = 5 studies), 1%; heart failure (HF) with preserved ejection fraction (n = 6), 12%; HF with reduced or mildly reduced ejection fraction (n = 2), 10%, conduction disorders warranting pacemaker implantation (n = 1), 2%; surgery for carpal tunnel syndrome (CTS; n = 3), 7%; hypertrophic cardiomyopathy phenotype (n = 2), 9%; aortic stenosis (AS) undergoing surgical or transaortic valve replacement (n = 7), 10%; autopsy series of "unselected" elderly individuals (n = 4), 15%. Many of these patients had ATTR–CA, but the percentage of cases with amyloid light–chain CA was far from negligible. Conclusions: Screening for CA in specific settings allows to identify a relatively high number of cases, in agreement with the notion that CA is not a rare disease. Many patients have ATTR–CA. Most studies focused on elderly subjects, given the clear relationship between age and the likelihood of CA. Men accounted for a high proportion of patients with CA, but women were quite represented.